(untitled) (Current Horticulture, 2024)
A field experiment was conducted to find out the effect of foliar application of organic liquids on growth, yield and quality of turmeric (Curcuma longa L.) cv. GNT-2 during 2019-20 at Regional Horticultural Research Station, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari, Gujarat, India. Randomized Block Design with three replications and eleven treatments, viz. panchagavya @ 4% (T1), panchagavya @ 5% (T2), novel organic liquid nutrients @ 4% (T3), novel organic liquid nutrients @ 5% (T4), jeevamrut @ 4% (T5), jeevamrut @ 5% (T6), humic acid @ 0.1% (T7), humic acid @ 0.2% (T8), cow urine @ 4% (T9), cow urine @ 5% (T10) and the control (T11) was followed. The novel organic liquid nutrients 5% (T4) registered significantly maximum plant height (93.64 cm at 150 DAP and 120.71 cm at 210 DAP) and maximum number of leaves/plant (6.27, 6.83 and 8.33) at 90, 150 and 210 DAP, respectively. However, maximum length of leaves (60.46 cm and 73.07 cm) was recorded at 150 and 210 DAP. Application of humic acid 0.2% (T8) gave maximum number of tillers/plant at 90, 150 and 210 DAP (1.27, 2.53 and 3.50, respectively). Substantial effect of foliar application of novel organic liquid nutrients at 5% (T4) gave more number of mother rhizomes/plant (3.53), number of finger rhizomes/plant (18.20), weight of mother rhizome (52.73 g), weight of finger rhizomes (248.67 g) with lowest number of finger rhizomes: number of mother rhizomes ratio (5.15) as well as fresh weight of rhizome (301.40 g/plant) with fresh rhizome yield (32.29 t/ha). The curcumin content in rhizomes (3.86%) as well as essential oil of rhizomes (3.23%) was recorded in 0.2 % humic acid (T8). The foliar application of 5% novel organic liquid nutrients was found economical, profitable and highly remunerative with maximum net returns of ` 6,54,732 and maximum benefit:cost ratio (4.29) as compared to rest of the treatments.